Acute effect of shockwave therapy on plantar pressure distribution and balance in hemiparetic individuals - Rosella, Brenda Góes [UNESP]; de Souza Vianna, Mariane Cherryne Neves [UNESP]; Scandiuzzi, Laura Mendonça [UNESP]; da Cruz, Douglas Cardoso [UNESP]; Pedroni, Cristiane Rodrigues [UNESP]; Faganello-Navega, Flávia Roberta [UNESP] (FapUNIFESP (SciELO), 2024)
Introduction: Cerebral vascular accident (CVA) is the second leading cause of death and is one of the diseases that most generate disability Hemiparesis is the most common motor deficit, and one of its characteristics is asymmetry in weight bearing and in the plantar sup-port area, leading to balance deficits. extracorporeal shockwave therapy (ESWT) has been shown to be effective in reducing post-stroke spasticity. Objective: To evaluate the effect of a ESWT session on the distribution of plantar pressure and on the static and dynamic balance of hemiparetic individuals after stroke. Methods: Twelve individuals with hemiparesis as a result of stroke in the chronic stage participated in the study. Data collection was divided into two days. On the first day, anamnesis and tests were performed: timed up and go (TUG), four square step test (FSST), and short physical performance battery (SPPB). After carrying out the tests, the distribution of plantar pressure was evaluated using baropodometry. Also on the first day, participants received ESWT in the muscle belly of the gastrocnemius muscle on the hemiparetic side. At the end of the ESWT session and after 7 days, the individuals were reassessed. Results: The results referring to the static and dynamic balance and baropodometry evaluations performed before, immediately after and one week after the application of ESWT did not show a significant difference between the three evaluations in any of the tests and in any of the moments performed. Conclusion: One ESWT session did not affect plantar pressure distribution and static and dynamic balance of hemiparetic individuals after stroke.
Efeito agudo da terapia por ondas de choque na pressão plantar e equilíbrio de indivíduos hemiparéticos
Keywords: Extracorporeal shockwave therapy; Postural balance; Stroke